Pelatihan Desain Flyer Dakwah Moderasi Beragama untuk Penguatan Pemahaman Moderasi Beragama Bagi Remaja Kota Metro - Has, Qois Azizah; Rachman, Evy (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This community service activity refers to one of the objectives of the Ministry of Religious Affairs in increasing the value of religious tolerance.Â  But unfortunately, based on the observations of youth in metro city, many do not understand the ins and outs of where the term religious moderation was born. The theology of religious moderation becomes ambiguous when no one understands the origin of the term. In fact, the term religious moderation is not much the same as the understanding of theology that already exists in Indonesia. In addition, the world of digital literacy has been very popular in metro society, especially teenagers. Unfortunately, many digital materials do not reflect the preaching of moderation and tend to contain radical provocations. This is because digital media users are minimal in spreading their da'wah through this digital world. So that the efforts, efforts and fighting spirit of religious moderation in instilling preaching in the digital world need to be improved. Therefore, this community service activity with the ABCD (Assed Based Community Development) method aims to increase the understanding of Metro city youth about the theological roots of religious moderation and can actualize it in the form of works in the form of digital flyers based on religious moderation. And the results of this service are in the form of works of teenagers packaged in the form of digital canva flyers containing moderation values for teenagers. And published on social media as a form of digitalization of religious moderation da'wah. Keywords: Da'wah Flyer, Religious Moderation, Digital Da'wah